WAYS OF SOLVING PROBLEMS OF TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
In our article, ways to solve the problems of teaching English vocabulary to young students are evaluated. Language learners are well aware that one of the main criteria in learning foreign languages is the vocabulary of the language being studied and its meaning and its practical application.